Usulan Perbaikan Waste dan Meningkatkan Kinerja pada Produksi Benang dengan Pendekatan Lean Six Sigma di PT Dhanar Mas Concern I - Ghina Syarifah; Endang Prasetyaningsih (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstract. PT Dhanar Mas Concern I is a company engaged in spinning cotton into yarn. Producing quality thread products is not easy, defects are often found during production. There are 6% -7% of defective products from total production, as well as waiting activities which are a waste. This research is expected to provide suggestions for improvements related to wastage of defective products and other waste. The lean six sigma approach is used to solve the problems found. The tools used include value stream mapping, 7 waste, process cycle efficiency (PCE), DPMO and sigma level, fishbone, 5W+1H, and visual control. The calculation results show a PCE value of 69% which can be said that it is still not maximally efficient. Meanwhile, the determination of the sigma level during June–July 2021 is 2.28, so it still needs to be increased to a standard sigma level of 3.4. The recommendations suggested are scheduling machine maintenance, conducting routine training for operators, making work standards in visual form, providing industrial portable evaporative air coolers, changing batch transfers and designing conveyors from the ring frame work station to the winding work station. Consultations were carried out with the Head of Production regarding recommendations for improvements, which could increase the PCE value from 69% to 84% and the sigma level from 2.28 to 2.48 which affected the productivity and quality of the yarn produced.. Keywords: lean six sigma, six sigma, process cycle efficiency, level sigma. Abstrak. PT Dhanar Mas Concern I merupakan perusahaan yang bergerak di bidang pemintalan kapas menjadi benang. Menghasilkan produk benang yang berkualitas bukanlah hal yang mudah, sering kali ditemukan produk cacat selama produksi. Terdapat 6%-7% produk cacat dari total produksi, serta aktivitas menunggu yang merupakan pemborosan. Penelitian ini diharapan dapat memberikan usulan perbaikan terkait pemborosan produk cacat dan pemborosan lainnya. Pendekatan lean six sigma digunakan untuk menyelesaikan permasalahan yang ditemukan. Adapun tools yang digunakan, diantaranya value stream mapping, 7 waste, process cycle efficiency (PCE), DPMO dan level sigma, fishbone, 5W+1H, dan visual control. Hasil perhitungan menunjukan nilai PCE sebesar 69% yang dapat dikatakan bahwa masih belum efisien dengan maksimal. Sementara penentuan level sigma selama bulan Juni–Juli 2021 sebesar 2.28, sehingga masih perlu ditingkatkan hingga standar level sigma sebesar 3.4. Rekomendasi yang disarankan yaitu mengadakan penjadwalan perawatan mesin, mengadakan pelatihan rutin kepada operator, membuat standar kerja dalam bentuk visual, menyediakan industrial portable evaporative air cooler, mengubah batch transfer dan merancang conveyor dari stasiun kerja ring frame menuju stasiun kerja winding. Konsultasi dilakukan bersama Kepala Produksi terkait rekomendasi perbaikan, dapat meningkatkan nilai PCE dari 69% menjadi 84% dan level sigma dari 2.28 menjadi 2.48 yang berpengaruh pada produktivitas dan kualitas benang yang dihasilkan. Kata Kunci: lean six sigma, six sigma, process cycle efficiency, level sigma.